(untitled) (Scientific journal of the Fergana State University, 2024)
In linguistics, in comparative linguistics carried out the large number of studies related to the linguistic world picture. Despite the studies of lexical-semantic, structural peculiarities of paremiological units, still it is little known about paremiological units related to the micro-field of "education" in Uzbek and English languages. In this article, considering this need, the structural structures, semantics and functions of paremiological units in two languages are thoroughly analyzed. In this analysis, the methods of contextual description, comparative, semantic and lingucultural analysis were used, units related to "education" in Uzbek and English languages were comparatively studied, their structural simple and complex types, semantic functions were clarified.